A Rescue Excavation at the Islamic Site of Umm Zweitineh in Central Jordan, 2012 - Khries, Hashem; Al-Gonmeen, Taher (Journal of Islamic Archaeology, 2023)
This paper draws on the preliminary results of the rescue excavation conducted by the Department of Antiquities at Umm Zweitineh in central Jordan in 2012. The goal of the excavation was to take urgent action regarding protecting the site as far as possible. Due to budget constraints, the excavation work lasted for only twenty days. The aim of the article is that of providing a clear regional picture of the Islamic settlement through the seventh/eighth and fourteenth centuries AD through retrieving information from the architectural remains and material culture. The architectural relics and material culture were unearthed under a dense layer of wreckage and accumulated debris because of previous construction work at the site. The accumulation deposits yielded a ceramic assembly of daily life vessels dating primarily to the Umayyad and Mamluk periods. Earlier pottery sherds belonging to the Roman and Byzantine periods have been also uncovered. Ceramic sherds from the Iron Age II sporadically appeared on topsoil. Besides the ceramic, other metal artifacts, including bronze vessels from different periods, have been unearthed. The Umayyad and Early Mamluk settlements were distinguishable because of the distinct corpus typical of both periods. Possible evidence of a religion building belonging to the Umayyad-period Christianity have been unearthed in Area B.